CRISPR Mediated Biosensing Toward Understanding Cellular Biology and Point‐of‐Care Diagnosis. Issue 47 (25th August 2020) - Dai, Yifan; Wu, Yanfang; Liu, Guozhen; Gooding, J. Justin
Abstract: Recent advances in CRISPR based biotechnologies have greatly expanded our capabilities to repurpose CRISPR for the development of biomolecular sensors for diagnosing diseases and understanding cellular pathways. The key attribute that allows CRISPR to be widely utilized is the programmable and highly selective mechanism. In this Minireview, we first illustrate the molecular principle of CRISPR functioning process from sensing to actuating. Next, the CRISPR based biosensing strategies for nucleic acids, proteins and small molecules are summarized. We highlight some of recent advances in applications for in vitro detection of biomolecules and in vivo imaging of cellular networks. Finally, the challenges with, and exciting prospects of, CRISPR based biosensing developments are discussed. Abstract : CRISPR, a sensing and actuating machine, mediates biosensing toward point‐of‐care diagnosis and understanding cellular biology.